KEBERLANJUTAN PROGRAM SISTEM INTENSIFIKASI POTENSI LOKAL (SIPLO) DALAM USAHATANI PADI (Oryza Sativa L) DI DESA JATISARI KECAMATAN PAKISAJI KABUPATEN MALANG - Harmono, Harmono; Pudjiastuti, Agnes Quartina; Khoirunnisa, Ninin (BUANA SAINS, 2024)
This study aimed to analyze the sustainability of the SIPLO program in rice cultivation in Jati Sari Village, Pakisaji District, Malang Regency. Data was collected from rice farmers participating in the SIPLO demonstration field in Jati Sari Village. The data was quantitatively analyzed using RAP-SIPLO, an improved version of RAP-FISH software, to determine the sustainability status of the SIPLO program. The results showed that the SIPLO program received a high score of 53.02 in terms of sensitive ITAS values of the sustainability indicators of the multidimensional scaling (MDS) from each of the following dimensions: ecological, economic, social, and technological; 51.33, 69.28, and 63.65. These figures indicate that the sustainability of the SIPLO program falls in the "sufficient" category. The SIPLO technique was first applied to rice (Oryza sativa L.) in Jati Sari Village, Pakisaji District, Malang Regency, and was found to be sufficiently effective.